Determination of The Water Quality Status of The Kalimalang River In Telaga Murni Recidence, Bekasi District - Nisa Nurhidayanti; Novi Justika Harini; Agus Riyadi (Proceeding International Pelita Bangsa, 2023)
The behavior of the people around the riverbanks, such as throwing garbage directly into the river body, and the river's proximity to steel-producing companies impacts river water quality. This research aims to determine the Kalimalang River water quality status in Telaga Murni housing. The sampling method used in this study is the Grab Sampling method with a combination of Purposive Sampling, which is taken from the most polluted points so that it is expected to obtain river water samples that best follow the conditions of river water quality from upstream to downstream. From the results of laboratory tests & calculations using the Storet method and Pollution Index, river water in Telaga Murni housing is classified as heavily polluted. The Phenol and Total Coliform values exceed the quality standards indicating contamination from domestic and industrial wastewater.